Microbial survival strategies in desiccated roots of Myrothamnus flabellifolia - Tebele, Shandry M.; Marks, Rose A.; Farrant, Jill M. (Frontiers in Microbiology, 2025)
IntroductionRoot-associated microbiomes are critical to plant vigor, particularly under drought stress. The spatial dynamics of microbial community diversity and composition are strongly influenced by plant root and environmental factors. While the desiccation tolerance of the resurrection plant Myrothamnus flabellifolia using leaf tissue has been previously investigated, the transcriptional responses of its root-associated microbiomes under desiccation remain completely unexplored.MethodsHere, we conducted metatranscriptome sequencing on root samples of M. flabellifolia collected in the field across four states: dry, desiccated, partially hydrated, and fully hydrated.ResultsBacterial transcripts dominated the root metatranscriptome across all conditions. Desiccated roots exhibited a significant increase in transcripts from Actinomycetota, whereas fully hydrated roots showed an enrichment of Pseudomonadota. Under desiccation, root-associated bacteria upregulated genes involved in antioxidant systems, trehalose biosynthesis, and hormonal regulation.DiscussionThese findings highlight microbial adaptive mechanisms to withstand extreme water loss. In contrast, the bacterial transcriptional response in hydrated roots was characterized by genes linked to peptidoglycan biosynthesis, sugar transporters, and chemotaxis. Taken together, our findings indicate that root-associated bacteria deploy defense mechanisms analogous to those of their host plant to adapt to extreme drought stress, highlighting their crucial role in plant resilience.